2012
DOI: 10.5455/medarh.2012.66.318-320
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Ultrasonography in Evaluation of Vitreo-retinal Pathologies

Abstract: Ultrasonography is useful part of ophthalmic examination for detection, evaluation and follow up of different vitreo-retinal pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 12 publications
0
11
1
1
Order By: Relevance
“…However, ultrasonography examination can change the initial treatment plan in 4.8% and subclassify diagnosis and aid with further surgical planning in 13% of patients scheduled for pars plana vitrectomy. 2 When considering only patients with poor visualization of the posterior segment, these figures are even higher at 9% and 20%, respectively. 2 These outcomes are consistent with previous studies that reported ultrasonography established or changed the management plan in 8% and subclassified the diagnosis in 13% of patients with various posterior segment pathologies including cataract and choroidal detachment.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…However, ultrasonography examination can change the initial treatment plan in 4.8% and subclassify diagnosis and aid with further surgical planning in 13% of patients scheduled for pars plana vitrectomy. 2 When considering only patients with poor visualization of the posterior segment, these figures are even higher at 9% and 20%, respectively. 2 These outcomes are consistent with previous studies that reported ultrasonography established or changed the management plan in 8% and subclassified the diagnosis in 13% of patients with various posterior segment pathologies including cataract and choroidal detachment.…”
mentioning
confidence: 95%
“… 2 When considering only patients with poor visualization of the posterior segment, these figures are even higher at 9% and 20%, respectively. 2 These outcomes are consistent with previous studies that reported ultrasonography established or changed the management plan in 8% and subclassified the diagnosis in 13% of patients with various posterior segment pathologies including cataract and choroidal detachment. 5 …”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Such PVD could have been missed in previous studies, due to the inability to detect the early PVD by either clinical examination or ultrasonography. Combined slitlamp biomicroscopy, OCT and ultrasonography provide reliable information regarding the state of the vitreoretinal interface and PVD presence in all stages, regardless of underlying vitreoretinal pathology …”
mentioning
confidence: 99%